Low-Cost Flexible Temperature Sensor Based on Printed Circuit Board Technology - Yu, Nam Chol; Son Guk Pak; Hyong Su Yu; Chol Min Jong; Jin Sim Kim (Journal of Power Electronics and Devices, 2023)
Air flow measurement is a crucial duty in many process monitoring systems. In applications like management of ventilation and air conditioning systems, robustness, convenience of use, and cost are major challenges calling for simple and effective sensor design. In this paper, we present a low-cost copper thick film flexible temperature sensor based on PCB (printed circuit board) technology. A new design is proposed to avoid defects in the resistive lead of the sensors. Detour leads are added to the resistive lead layout of the sensor. There were improvements in the actual extract rate of the sensor in the fabrication process and the accuracy of the initial resistance of the sensor (the resistance at 0°C). The actual extract rate is 100% in the sensor fabrication process by handling and deviations of the initial resistances (R0=100Ω) are less than 0.1Ω in the fabricated sensors. However, there is still opportunity for future advancement in both technology and sensor design. The first experimental results of sensor prototypes demonstrate that the repeatability of PCB manufacturing processes is essentially suitable for using copper traces as sensors.